Effect of additional seaweed on the chemical properties of dodol pisang mas bali (Musa paradisiaca L.) - Syahlan, Irfan; Sari, Desy Ambar; Marianah, Marianah (UNIVERSITAS MUHAMMADIYAH MATARAM, 2023)
Dodol is a processed food belonging to the type of semi-wet food, consisting of a mixture of flour, coconut milk and sugar that is dried by cooking. Based on the main ingredients, dodol is divided into two groups, namely dodol made from glutinous rice and dodol made from fruits. One type of fruit that can be used to make dodol is banana. The aim of this study was to determine the effect of seaweed addition on the chemical and organoleptic properties of Mas Bali Banana Dodol. This study was designed using a completely randomised design (CRD) with a single factor, namely the addition of seaweed in the production of banana dodol, consisting of 5 treatments as follows 5% (P1), 10% (P2), 15% (P3), 20% (P4) and 25% (P5) seaweed addition. The parameters measured included chemical properties (moisture content, ash content and fibre content) and organoleptic tests (aroma, taste, colour and texture). The test results were then analysed using ANOVA at a 5% real level and, if there were significant differences between treatments, further tested using BNJ at the same real level. Based on the results of the analysis, it is known that the addition of seaweed has a significant effect on all the chemical and organoleptic properties of the grapefruit-banana dodol studied. The higher the addition of seaweed, the higher the water content, ash content and fibre content of the grapefruit-banana dodol, while the colour of the dodol becomes darker. In terms of texture, the higher the amount of seaweed used, the more chewy the texture of the resulting grapefruit banana dodol. In conclusion, P5 is the best treatment, most preferred by the panelists, with a seaweed addition of 25%, giving a moisture content of 47.33%, ash content of 2.28%, fibre content of 13.76%, with a preferred flavour and taste, a very brown dodol colour and a chewy texture.